Recomendações de fertilização fosfatada e potássica para as principais culturas de grãos sob sistema plantio direto no Paraguai - Riquelme, Ursino Federico Barreto (2008)
The recommendations of fertilization have as main purpose to facilitate and aid the decisions about application of fertilizers necessary to obtain yields of maximum economic efficiency. Pointing out the importance of the numerical tables indications, should be also important the crops and area history, the history of fertilizations and calcareous use, the yields obtained and expected, the farmer social-economic conditions, the management system and soil type, the area climatic conditions and the environmental impact of the technology used. With the no-till (SPD) adoption in Paraguay, questions appeared about the use of fertilizers technical recommendations, especially of phosphorus (P) and potassium (K), considering that this tables had been elaborated having as base researches accomplished with experiments carried out in soil conventional tillage system (SC). This research aimed to generate recommendations of phosphate and potassium fertilization through experiments of calibration in seven places in the Região Oriental of Paraguay. The experiments, in no-till, were carried out since 2003 to 2006, in soils with different texture and initial levels of fertility, in representative areas of grains crops production and in areas with known history of no-tillage adoption in the country. In the Misiones Department experiments were carried in two areas (one of medium and another of low fertility, both with the same texture); in the Itapúa Department in two areas (one of high and another of low fertility, with different texture); in the Alto Paraná Department (two areas of low fertility, but with the same texture) and one of low fertility in the Amambay Department. The experimental design used was randomized blocks, with subdivided plots and three replicates. For phosphorus, the main plots were fertilized with five doses of P (0, 50, 100, 200 e 400 kg ha-1 of P2O5) with the purpose to create levels of fertility and seeded with wheat later. In the sub plots were applied four doses of P (0, 40, 80 e 120 kg ha-1 of P2O5) during corn and soybean seeding, aiming to obtain the response curve. For potassium, the treatments were five doses of K2O (0, 25, 50, 75 and 100 kg ha-1), with applications in soil surface before the crops seeding. The doses were applied every planting, respecting the same amounts and in the same plots, which varied in the second phase of the experiments, for the winter of 2005 and summer of 2005-2006. To obtain more points in the response curves in the project second phase, an application of 120 kg of phosphorus was done in the plots with level 200 kg of P2O5, and in the plots of K2O were applied 25 kg of K2O. Were sampled ten soil samples by plot in the depth of 0 to 10 cm before seeding and after crop harvest. The P build level was more influenced by P start level and by areas fertilization history than soil texture. In the soils with low P level and with no fertilization history was necessary to apply 35,4 kg of P2O5 ha-1 to increase 1 mg dm-3 of P in the soil. On the other hand, to soils with intermediate to high level and history of previous fertilizer application was necessary to apply 20,3 kg of P2O5 ha-1 to increase 1 mg dm-3 of P in the soil. Was necessary to add 27,85 kg of P2O5 ha-1 to increase 1 mg dm-3 of P in the soil, when the distinction between soils with or without history of fertilization was not done. To reach the P critical level in the soil, the addition of 210 kg ha-1 of P2O5 is recommended for class "very low", 105 kg ha-1 for class "low" and 30 kg ha-1 for class "medium". The critical level of P was higher than that established by the ROLAS, and the influence of the soil texture was smaller than that previewed by the ROLAS. The critical level for soils with 410-600 g kg- 1 of clay (Class 1) was 12 mg dm-3 and for soils of 210 a 400 g kg-1 of clay (Class 2) was 15 mg dm-3. The critical level determined for soybean, corn and wheat crops were of 15, 10 and 12 mg dm-3, respectively. The K critical level determined by Mehlich-1 for wheat, corn and soybean under no-tillage in the Paraguay is 75 mg dm-3. To reach the K critical level in the soil, the addition of 250 kg ha-1 of K2O is recommended for class "very low", 125 kg ha-1 for class "low" and 40 kg ha-1 for class "medium". It is necessary 5 kg ha-1 of K2O to increase one mg dm-3 of its level in the soil. In K2O soil levels upper 150 mg dm-3, the plants presents low probability of answer to potassium fertilizers application. Smaller relative and absolute yields were obtained with wheat after soybean than after corn.